2020
DOI: 10.7150/ijms.50260
|View full text |Cite
|
Sign up to set email alerts
|

Herbal plants coordinate COVID-19 in multiple dimensions - An insight analysis for clinically applied remedies

Abstract: The use of multipronged measures, including traditional Chinese medicine (TCM), has greatly increased in response to the COVID-19 pandemic, and we found the use of TCM and is positively correlated with the regional cure rate in China (R=0.77, P <10 -5 ). We analyzed 185 commonly administered TCM recipes comprised of 210 herbs nationwide to reveal mechanistic insight. Eight out of the 10 most commonly used herbs showed anti-coronavirus potential by intersecting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…The proportion of TCM applications in Wuhan city, Hubei province, and China was 89.10%, 91.64%, and 92.41%, respectively (19,21,46,47). HSBDF was gradually implemented in the treatment process of the first batch of Chinese medicine medical teams in Jinyintan Hospital and Dongxihu square cabin hospital (21,48).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of TCM applications in Wuhan city, Hubei province, and China was 89.10%, 91.64%, and 92.41%, respectively (19,21,46,47). HSBDF was gradually implemented in the treatment process of the first batch of Chinese medicine medical teams in Jinyintan Hospital and Dongxihu square cabin hospital (21,48).…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled inflammation can trigger a cytokine storm, leading to cytokine release syndrome ( Zuo et al, 2020 ), tissue damage to the heart, liver, and kidneys, respiratory and multiple organ failure, and even death ( Schett et al, 2020 ; Huang et al, 2020b ). Therefore, anti-inflammatory drugs are as important as antiviral drugs for critical patients ( Table 4 )( Ren et al, 2020 ; Zhang et al, 2020 ; Chikhale et al, 2021 ; Wang et al, 2021c ).…”
Section: Research Status Of Antiviral Tcmsmentioning
confidence: 99%
“…TCM mainly exerts the effect of anti-viral infection indirectly by regulating and restoring the equilibrium of the body's immune system [ 13 ]. Using of Chinese medicine was confirmed to be associated with regional cure rate in China [ 14 ]. A series of clinical trials, case reports and observational studies confirmed the broad prospects of Chinses medicines in preventing or treating COVID-19 in different periods [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%